2015
DOI: 10.1021/acs.jpca.5b03456
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Second-Order Nonlinear Optical Properties and Switching Ability of a Series of Dithienylethene-Containing, Cyclometalated Platinum Complexes: A Theoretical Investigation

Abstract: The second-order nonlinear optical (NLO) properties of a series of dithienylethene- (DTE-) containing Pt(II) complexes have been investigated by density functional theory calculations. The first hyperpolarizabilities β of studied systems can be greatly enhanced by simple ligand substitutions. Because of the nature of DTE units, the β values also can be varied by the use of lights in the studied systems. The highest β difference between photoisomers can over 1000 × 10(-30) esu, with the contrast around five tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, the UV–vis spectra computed with the B3LYP functional (Figure ) perfectly reproduce the experimental ones, with respect to not only the relative peak intensities but also the band positions, which allows us to accurately assign electronic transition character of compound 1 . Studies have shown that the 6-31+G­(d) basis set is sufficient to determine the nature of electronic transitions for organic compounds. Thus, the B3LYP/6-31+G­(d) method was used in the calculations of UV–vis spectra of the studied compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, the UV–vis spectra computed with the B3LYP functional (Figure ) perfectly reproduce the experimental ones, with respect to not only the relative peak intensities but also the band positions, which allows us to accurately assign electronic transition character of compound 1 . Studies have shown that the 6-31+G­(d) basis set is sufficient to determine the nature of electronic transitions for organic compounds. Thus, the B3LYP/6-31+G­(d) method was used in the calculations of UV–vis spectra of the studied compounds.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the research focus of nonlinear optical materials is mainly focused on the construction of organic molecules containing electron donor (D), electron acceptor (A) and π-conjugation [7]. For example, D-π-A, A-π-D-π-A, D-π-A-π-D and other organic molecules [8] [9], focus on increasing the third-order NLO coefficients (second-order hyperpolarizability), so as to improve the optical properties of organic materials [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear response of molecules to electromagnetic fields has been studied over the last two decades. It provides a way for amplification, modulation and changing the frequency of optical signals (Liu et al, 2011; Lin et al, 2015). Materials with massive hyperpolarizabilities have found applications in optoelectronics, such as optical switching for optical computing or high-density optical recording.…”
Section: Introductionmentioning
confidence: 99%